ORGANIZATION OF THE PUBLIC PROCUREMENT PROCESS AT THE LEVEL OF THE CONTRACTING AUTHORITIES IN ROMANIA. PARTICULARITIES AND SOLUTIONS FOR THE MANAGEMENT OF PUBLIC PROCUREMENT PROCEDURES ORGANIZED IN THE CONTEXT OF EMERGENCY OF COVID-19 CRISIS - Ceocea, Costel; Ceocea, Raluca Alexandra; Vatamaniuc, Adrian; Mihălaș, Vasile (Studies and Scientific Researches. Economics Edition, 2020)
The normative framework applicable to public institutions imposes an approach to public procurement management aimed at awarding public procurement contracts in conditions of economic and social efficiency. Achieving the objectives set at the level of the organization, in accordance with the principles underlying the award of public procurement contracts is conditioned by the adoption and implementation of specific procedures, mainly oriented towards the organization of decision-making processes. In the context of the crisis triggered by the new Coronavirus SARS-CoV-2, contracting authorities were forced to organize public procurement processes, in a matter of urgency, on a procedural background less oriented towards adopting fast and efficient decisions, with negative effects both on the available financial resources and on the process of ensuring the flow of products, services and works corresponding to the rhythm imposed by the urgent needs of public institutions involved in managing the effects of the health crisis. This paper aims at individualize the decision-making process in the field of public procurement in Romania, in order to identify models of good practice, procedures and support working tools for optimizing the public procurement process carried out at the level of contracting authorities in a matter of emergency.